2009
DOI: 10.4161/cbt.8.9.8210
|View full text |Cite
|
Sign up to set email alerts
|

PIM1 Protein Kinase regulates PRAS40 phosphorylation and mTOR activity in FDCP1 cells

Abstract: PIM1 is a serine/threonine kinase that has diverse biological roles in cell survival, proliferation and differentiation. PIM1 has been implicated in early transformation and tumor progression in haematopoietic malignancies and prostate carcinomas. The ability of PIM1 to regulate these processes is thought to be in part secondary to its activity in stimulating 4EBP1 phosphorylation and enhancement of protein synthesis. Because 4EBP1 is an mTOR substrate, we have investigated how PIM1 might regulate this latter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
115
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(131 citation statements)
references
References 56 publications
11
115
0
5
Order By: Relevance
“…We further identify PRAS40 as a molecular link between A␤ accumulation and mTOR hyperactivity. Toward this end, when PRAS40 is phosphorylated by Akt or PIM-1 at Thr-246, it does not bind to mTOR and hence release its inhibitory effects on mTOR activity (14,15,65). Our data strongly support the conclusion that PRAS40 phosphorylation plays a key role in the A␤-induced mTOR hyperactivity.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We further identify PRAS40 as a molecular link between A␤ accumulation and mTOR hyperactivity. Toward this end, when PRAS40 is phosphorylated by Akt or PIM-1 at Thr-246, it does not bind to mTOR and hence release its inhibitory effects on mTOR activity (14,15,65). Our data strongly support the conclusion that PRAS40 phosphorylation plays a key role in the A␤-induced mTOR hyperactivity.…”
Section: Discussionsupporting
confidence: 75%
“…The data presented suggest that the A␤-induced alteration in mTOR activity in the 7PA2 cells and in the 3xTg-AD mice may be mediated by PRAS40 phosphorylation, which is physiologically phosphorylated by Akt and by the protein kinase PIM-1 (64,65). To better understand the role of PRAS40 in the A␤-mediated mTOR hyperactivity, we injected concentrated FIGURE 4.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, Pim kinases show similar substrate specificity as AKT. For example, a recent study revealed that overexpression of Pim-1 increased PRAS40 phosphorylation at Thr246, an AKT phosphorylation site (Zhang et al, 2009). In this study, we observed that Pim deficiency reduced PRAS40 phosphorylation at Thr246 in v-Abl transformants (Supplementary Figure S7).…”
Section: Discussionsupporting
confidence: 67%
“…[30][31][32][33] Most recent work suggests that phosphorylation of the proline-rich Akt substrate 1 (PRAS1) might also have the potential to block apoptosis of murine factor-dependent hematopoietic progenitor cells (FDCP-1). 34 In addition, PIM1 seem to impair the activity of the apoptosis signaling kinase 1 (ASK1), by direct phosphorylation, resulting in protection from H2O2-induced cell death of H1299 lung cancer cells. 35 Intriguingly, overexpression of PIM1 also stimulated cell death signaling in Rat1 fibroblasts elicited by c-MYC most probably through interaction and modification of the Cdc25A cell cycle phosphatase.…”
mentioning
confidence: 99%